C-Reactive Protein and Procalcitonin as Markers for Post-Bronchoscopic Complications: A Literature Review - Indriani, Sri Indah; Yovi, Indra; Syaf, Syarlidina; Simatupang, Elvando Tunggul Mauliate (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2024)
In the respiratory system, bronchoscopy is a basic procedure utilized for both diagnostic and therapeutic purposes. Despite being a generally safe procedure, bronchoscopy can result in complications that range in severity from moderate to severe. Pulmonary infection is among the potential complications that can happen after a bronchoscopy procedure. An incidence of 0.2% to 5.2% has been described typically for complications such as empyema, lung abscess, and pneumonia that may develop after bronchoscopy procedures. Although these complications are uncommon, their prognosis can be quite bad. The risk of pulmonary infection, specifically pneumonia, has been related in several studies to sepsis and mortality in patients enduring bronchoscopy procedures. The initiation of the infection exposure process into the lung can be assisted through a variety of factors, including the underlying diagnosis and the type of intervention performed during the bronchoscopy procedure. A critical complication that needs additional consideration is the potential transmission of infection through bronchoscopy procedures. It is beneficial to consider prophylactic antibiotics before a procedure due to the possibility that infectious agents will be transferred from one patient to another. Antibiotic prophylaxis may involve the utilization of C-reactive protein (CRP) and Procalcitonin (PCT) testing as determining parameters. Serial PCT and CRP 24–96 hours post-bronchoscopy procedure might help to determine one of the post-bronchoscopy complications.